Binding Error-Induced Control States - Anna Foerster; Moritz Schiltenwolf; David Dignath; Roland Pfister (Journal of Cognition, 2022)
Binding and retrieval of stimulus features, response features, and their attentional weighting tune cognitive processing to situational demands. The two mechanisms promote successful actions, especially in situations in which such actions depend on controlled processing. Here we explored binding and retrieval of attentional control states that follow from erroneous actions. By definition, such errors are characterized by insufficient cognitive control but at the same time, error detection has been shown to trigger corresponding adjustments to prevent future failures. We reanalyzed existing datasets and conducted a novel experiment to investigate whether error-induced control states become bound to task-relevant stimuli. Results point towards a binding and retrieval of error-induced control states; however, the effect appears to be less reliable than for binding and retrieval of specific stimulus and response features. We discuss potential implications and alternative interpretations in terms of a mediating impact of error-induced control.